THE PLACE OF «SBERBANK» ON THE MODERN FINANCIAL MARKET - Ekaterina Kalashnikova; Daria Teslenko (Вестник Северо-Кавказского федерального университета)
This article describes the position of Sberbank in the financial market, reflecting its significance for the Russian economy. At the same time, the financial and investment activities of the bank have been analyzed, which give a general idea of its status for today, as well as an analysis of the financial performance of the research object, and the share of Sberbank in the banking market. The analysis of the bank's assets and liabilities, analysis of the structure of liabilities and equity of the bank, revealed the main development trends of PJSC "Sberbank". The search for faces and the role of financial management, investment portfolio, and banking services is determined. It is concluded that the boundary between liquidity, profitability and risk is found, which allows to find the optimal ratio between these indicators. It tells about Sberbank to date, which it underwent signiicant changes and replaced everything that ever reminded of the savings banks with which this bank was associatedfor a long period of time, about its rapid adaptation to changes and the ability to move swiftly forward. The fact that Sberbank not only monitors the current trends of the market, but also seeks to get ahead of them due to a good orientation in the preferences of customers.